Prevalence and characterisation of microfibres along the Kenyan and Tanzanian coast - KeChi-Okafor, Chimdia; Khan, Farhan R.; Al-Naimi, Usama; Béguerie, Victor; Bowen, Libby; Gallidabino, Matteo D.; Scott-Harden, Simon; Sheridan, Kelly J. (Frontiers in Ecology and Evolution, 2023)
Microplastic pollution is ubiquitous, with textiles being a major source of one of the dominant microplastic types - microfibres. Microfibres have been discovered in the aquatic environment and marine biota, demonstrating direct infiltration in the environment. However, the impact of non-plastic microfibres have been overlooked until recently despite their prevalence and the ecotoxicological risk posed by chemical dyes and finishes used during processing. During an expedition from Lamu to Zanzibar (East Africa), a citizen science strategy was employed to innovate, educate, and influence microfibre pollution reform through The Flipflopi project, a circular economy effort to stop the use of single-use plastic. Simple sampling methods were developed to replace costly equipment, which local citizens could use to partake in the collection and sampling of surface water samples from the previously understudied Kenyan and Tanzanian coast. To maintain the reliability of samples and to minimize contamination, a forensic science strategy was embedded throughout the methodology of the study, collection, and analysis of the samples. A total of 2403 microfibres from 37 sites were recovered and fully characterised with 55% found to be of natural origin, 8% regenerated cellulosic and 37% synthetic microfibres. Natural microfibres were in higher abundance in 33 of the 37 sampled sites. Congruent with recent studies, these findings further support the need for greater understanding of the anthropogenic impact of natural microfibres.